Annual Plan 1967-68 Progress Report - Planning Commission (Planning commission, 1967)
Since the inception of Planning in 1951-52, the economy of Punjab has maintained steady progress inspite of the setbacks on account of occasional unfavourable weather conditions, Indo-Pakistan War and the recession which hit the industrial sector. Output of food grains during 1967-68 reached the record level of 53.68 lakh tonnes or about 29 per cent more than the 1966-67 level of 41.78 lakh tonnes.
Planning Department Government of Punjab